Connections Across Eurasia : - Liu, Xinru (McGraw-Hill, 2007)
This first edition text examines the remarkable histories of the societies and peoples who fostered Eurasian trade and communication in the almost two millennia before 1500 C.E. A study in the early history of “globalization,” the commercial and cultural exchanges explored in this volume provide students not only with a greater knowledge of the past, but also a deeper understanding of our world today.